2022
DOI: 10.1007/s40477-022-00684-1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis on the effectiveness of ultrasound-guided versus landmark corticosteroid injection in the treatment of shoulder pain: an update

Abstract: Background Corticosteroid (CS) can be injected in a blind fashion (landmark-guided) or with ultrasound (US) guidance, and this may contribute to varying clinical results. We conducted this systematic review and meta-analysis to assess the effectiveness of US-guided versus landmark CS injections in the treatment of adult patients with shoulder pain. Methods We searched MEDLINE (via PubMed), Scopus, Web of Science, EBSCO, and Cochrane Library for randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…26 Similar to this meta-analysis, a 2023 systematic review in shoulder pain comparing the two techniques demonstrated a significant reduction in pain [SMD À0.48, 95% CI (À0.79, À0.17)] and functional improvement [SMD 0.35, 95% CI (0.05, 0.65)], favouring the ultrasound-guided injection. 27 In a 2018 narrative review related to ultrasound-guided injection in sports medicine, superior clinical outcomes were noted for the glenohumeral joint, the subacromial space, the biceps tendon sheath and the joints of the hand and wrist, the knee, ankle and foot. 28 In addition to the difference in clinical outcomes between the two techniques, our meta-analysis also demonstrated the significant difference in procedure-related pain which is important for patient's acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…26 Similar to this meta-analysis, a 2023 systematic review in shoulder pain comparing the two techniques demonstrated a significant reduction in pain [SMD À0.48, 95% CI (À0.79, À0.17)] and functional improvement [SMD 0.35, 95% CI (0.05, 0.65)], favouring the ultrasound-guided injection. 27 In a 2018 narrative review related to ultrasound-guided injection in sports medicine, superior clinical outcomes were noted for the glenohumeral joint, the subacromial space, the biceps tendon sheath and the joints of the hand and wrist, the knee, ankle and foot. 28 In addition to the difference in clinical outcomes between the two techniques, our meta-analysis also demonstrated the significant difference in procedure-related pain which is important for patient's acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…Though it ranks third in orthopedic practice, shoulder pain is a prominent cause of musculoskeletal discomfort. 1 Shoulder discomfort is a common, functionally crippling condition affecting people of all ages and activity levels, with the main cause being Subacromial Impingement Syndrome (SIS). 2 Adhesive capsulitis, shoulder instability, arthritis, and rotator cuff disorderswhich can include tendinopathy, partial tears, and total tears-are some of the illnesses that can cause persistent shoulder discomfort.…”
Section: Introductionmentioning
confidence: 99%